Hydrogen embrittlement behaviors at different deformation temperatures in as-quenched low-carbon martensitic steel. (15th January 2022) - Momotani, Yuji; Shibata, Akinobu; Tsuji, Nobuhiro
Abstract: The present study investigated hydrogen-related fractures at different deformation temperatures ranging from −100 °C to 100 °C in low-carbon martensitic steel. The sensitivity to hydrogen embrittlement increased as the temperature decreased from 100 °C to 0 °C, while it decreased as the temperature decreased further below 0 °C. We characterized the fracture surface types from the morphological and crystallographic aspects and found that the fraction of hydrogen-embrittled surfaces exhibited a similar temperature dependence on the sensitivity to hydrogen embrittlement. The qualitative discussion suggested that the degree of hydrogen accumulation exhibits a peak value in the medium temperature range, which has the same tendency as the sensitivity to hydrogen embrittlement confirmed experimentally. Thus, we proposed that the effect of deformation conditions on the sensitivity to hydrogen embrittlement could be explained on the basis of the hydrogen accumulation behavior. Graphical abstract: Image 1 Highlights: Sensitivity to hydrogen embrittlement becomes maximum in medium temperature range. Hydrogen promotes not only intergranular fracture but also typical cleavage fracture. Hydrogen accumulation behavior closely relates with hydrogen embrittlement property.